2022
DOI: 10.3389/fbioe.2022.914450
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Cell-Cycle Regulation in Neonatal Large Mammals: Single Nucleus RNA-Sequencing Data Analysis via an Artificial-Intelligence–Based Pipeline

Abstract: Adult mammalian cardiomyocytes have very limited capacity to proliferate and repair the myocardial infarction. However, when apical resection (AR) was performed in pig hearts on postnatal day (P) 1 (ARP1) and acute myocardial infarction (MI) was induced on P28 (MIP28), the animals recovered with no evidence of myocardial scarring or decline in contractile performance. Furthermore, the repair process appeared to be driven by cardiomyocyte proliferation, but the regulatory molecules that govern the ARP1-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…Then, prioritization needs to be performed only using the domainknowledge available network to generate hypotheses. Cardiac regeneration, which focuses on cardiomyocyte proliferation, case-study is an example when a significant biological process, not a disease, that does not naturally happen in matured mammals (Porrello et al, 2011;Lam and Sadek, 2018;Ye et al, 2018;Zhu et al, 2018;Zhao et al, 2020;Nakada et al, 2021;Nguyen et al, 2022). In this case, the focus is finding the regulating mechanism to create new cells and to apply this knowledge in biomedical engineering research.…”
Section: Discussionmentioning
confidence: 99%
“…Then, prioritization needs to be performed only using the domainknowledge available network to generate hypotheses. Cardiac regeneration, which focuses on cardiomyocyte proliferation, case-study is an example when a significant biological process, not a disease, that does not naturally happen in matured mammals (Porrello et al, 2011;Lam and Sadek, 2018;Ye et al, 2018;Zhu et al, 2018;Zhao et al, 2020;Nakada et al, 2021;Nguyen et al, 2022). In this case, the focus is finding the regulating mechanism to create new cells and to apply this knowledge in biomedical engineering research.…”
Section: Discussionmentioning
confidence: 99%
“…AI Autoencoding identified 10 cardiomyocyte clusters (denoted CM1-CM10), one of which (CM1) comprised 62.91% of the cardiomyocytes present in AR P1 hearts on P28 but was essentially absent in all other injury groups and at all other timepoints. In comparison, two other clusters (CM2 and CM10) collectively encompassed 89.62% of cardiomyocytes in AR P1 MI P28 hearts on P30 40 . Notably, CM1 cardiomyocytes were also enriched for the expression of three genes (TBX5 68 , 69 , TBX20 70 , 71 , and ERBB4 72 ) that contribute to the proliferation of cardiomyocytes in fetal and neonatal mouse hearts.…”
Section: Resultsmentioning
confidence: 92%
“…CM1 cells for which y > 0.1 were categorized as CM1→2, CM1 cells for which y < − 0.1 were categorized as CM1→10, and all other CM1 cells were categorized as inconclusive; then, CM2 cells were combined with CM1→2 cells (CM2 + 1→2), CM10 cells were combined with C1→10 cells (CM10 + 1→10), w and b were re-computed via formulas 2 – 4 with the combined cell populations serving as the predefined positive (CM2 + 1→2, y = 1) and negative (CM10 + 1→10, y = − 1) cell populations, y was recalculated for CM1 cells, and the procedure was repeated until the CM1→2, CM1→10, and inconclusive categories did not change. The results from our AI Semisupervised Learning Model 40 indicated that most (84.78%) CM1 cardiomyocytes would likely follow the CM1→2 trajectory, while the remainder (15.22%) followed the CM1→10 trajectory 40 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations